2019
DOI: 10.1002/mame.201900325
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Property–Process Relationship for Blown Films of Bimodal HDPE and Its LLDPE Blend

Abstract: Blown films of bimodal‐high‐density polyethylene (HDPE) (BPE) and its blend containing 40 wt% of linear low‐density polyethylene (LLDPE) are prepared in various neck‐heights (NHs). The crystal structures of both films are investigated in detail using small‐angle X‐ray scattering and wide‐angle x‐ray diffraction techniques. The results show that the blending of LLDPE notably modifies the crystal structure of BPE, including crystal density (ρc), crystallite size of the 110 plane (〈L110〉), thickness of the lamell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
(79 reference statements)
0
4
0
Order By: Relevance
“…In the literature, increased interest in such compositions is associated with the lower cost of polymers and the possibility of combining the positive properties of chemically similar types of PE, that have different density, molecular weight, rheological and performance properties, in one material. Mixtures of low-density polyethylene (LDPE) with monomodal copolymers of α-olefins LLDPE (butene-1, hexene-1, octene-1), high-density polyethylene (HDPE) with LDPE [ 7 , 8 , 9 ], HDPE with LLDPE [ 2 , 7 , 10 ] have been studied and characterized in detail and are widely used in film, membrane, and packaging production [ 11 , 12 , 13 , 14 ]. In these works, considerable attention is paid to the analysis of their rheological, mechanical, thermal, structural and morphological properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, increased interest in such compositions is associated with the lower cost of polymers and the possibility of combining the positive properties of chemically similar types of PE, that have different density, molecular weight, rheological and performance properties, in one material. Mixtures of low-density polyethylene (LDPE) with monomodal copolymers of α-olefins LLDPE (butene-1, hexene-1, octene-1), high-density polyethylene (HDPE) with LDPE [ 7 , 8 , 9 ], HDPE with LLDPE [ 2 , 7 , 10 ] have been studied and characterized in detail and are widely used in film, membrane, and packaging production [ 11 , 12 , 13 , 14 ]. In these works, considerable attention is paid to the analysis of their rheological, mechanical, thermal, structural and morphological properties.…”
Section: Introductionmentioning
confidence: 99%
“…In these works, considerable attention is paid to the analysis of their rheological, mechanical, thermal, structural and morphological properties. A special place in these studies is occupied by the studies of compatibility of components of the compositions [ 12 , 13 , 14 ], and in the case of ternary copolymers of LLDPE, the identification of the features of interdiffusion with HDPE. At the same time, HDPE obtained on titanium–magnesium Ziegler–Natta catalysts can be presented both as a homopolymer of ethylene with a narrow average molecular weight distribution (MWD) and as a copolymer of ethylene with α-olefin with a wide MWD (more often bimodal), which differ in the level of molecular weights, the presence of branching and compositional heterogeneity, which ultimately determines the properties of these PEs.…”
Section: Introductionmentioning
confidence: 99%
“…[ 9, 14, 15 ] Defoor et al [ 16 ] demonstrated that the core thickness of LLDPE crystalline lamellae decreases with increasing short‐chain branching content. Furthermore, LLDPE blending with different polyethylene components has been widely studied, [ 17–24 ] and the mechanical and optical properties of materials can be improved by blending. Guanghaoshen et al [ 13 ] blended high‐density polyethylene (HDPE) and LLDPE and found that cocrystallization occurred at all ratios even when the two components had a considerable difference in short‐chain branching distribution.…”
Section: Introductionmentioning
confidence: 99%
“…To design and control various phase structures, tremendous efforts have been devoted to obtain spheres, [ 13,14 ] cylinders, [ 15,16 ] bilayers, [ 17,18 ] lamellae, [ 19,20 ] gradient porous structures, [ 21 ] cocontinuous structures, [ 22,23 ] and sea‐island structures, [ 24,25 ] in polymer blends. For example, Yao et al.…”
Section: Introductionmentioning
confidence: 99%